No nutritional benefits of egg cannibalism for Coleomegilla maculata (Coleoptera: Coccinellidae) on a high-quality diet. Issue 3 (11th September 2017) - Abdelwahab, A.H.; Michaud, J.P.; Bayoumy, M.H.; Awadalla, S.S.; El-Gendy, M.
Abstract: Egg cannibalism serves various functions in the Coccinellidae. Here we examined the fitness consequences of egg cannibalism by neonates, fourth instar larvae, and prereproductive adults of Coleomegilla maculata DeGeer, with beetles fed a diet of Ephestia kuehniella Zeller eggs. Cannibalism of two eggs by neonates had no effect on development, and cannibalism of five eggs by fourth instars did not benefit any aspect of reproduction, but delayed pupation slightly. Cannibalism of eggs by pre-reproductive adults had no effect on reproductive success in any combination of reciprocal crosses of cannibals and non-cannibals. Females did not recognize, nor avoid consuming, their own clutches, and cannibalism propensity did not change following mating and onset of oviposition in either sex. These results contrast with those for more strictly aphidophagous species in which larvae gain developmental benefits, and females may recognize and avoid filial egg clusters while using cannibalism to interfere with conspecific females, whereas males reduce egg cannibalism after mating because they cannot recognize filial clusters. Egg cannibalism may confer developmental benefits to C. maculata when diet is suboptimal, as previously shown, but no such benefits were evident on the high-quality E. kuehniella egg diet. Female C. maculata do not require aphids to reproduce and distribute their eggs broadly in the environment, given that larvae can develop on pollen and non-aphid prey. Thus, C. maculata is not subject to the intraspecific competition that selects for cannibalism in more aphidophagous species, and also lacks many secondary adaptations associated with the behaviour.